Effect of high-carbon layer microstructure obtained by arc welding using carbon fiber materials, the parameters of durability to abrasion environment - Савуляк, В.І.; Шенфельд, В.Й.; Панасюк, С.О. (Problems of Tribology, 2016)
The aim is to determine the effect of high-carbon layer microstructure obtained by arc welding using carbon fiber materials, the parameters of durability to abrasion environment.Introduction article shows the importance of the problem by exploring the authors.The main article provides partial equipment on which tests conducted on samples of high carbon wear. Installation is developed and used to improve the wear resistance technology department of Vinnytsia National Technical University. High carbon samples had different structure. There are modes in which the samples tested for wear.Shown wear high carbon intensity of coverage provided coverage changes structural components in abrasive environments. Further highlights high wear resistance carbon coatings with different structures abrasion protection (by rubbing 14,000 m). Also, an analysis of the impact of each layer of high-microstructure obtained by arc welding using carbon fiber materials, the parameters of durability to abrasion environment.At the end of the article, the authors suggest the findings of the study. Analysis of the data showed that a greater wear resistance under abrasive environment with coverage of ledeburytnoyu structure. The greatest intensity of wear have a covering of high carbon martensite-austenitic structure.